Reply to Landry et al. Findings from Diet Comparison Difficult to Interpret in the Absence of Adherence Assessment. Comment on “Tricò et al. Effects of Low-Carbohydrate versus Mediterranean Diets on Weight Loss, Glucose Metabolism, Insulin Kinetics and β-Cell Function in Morbidly Obese Individuals. Nutrients 2021, 13, 1345” - Domenico Tricò (MDPI AG, 2021)
We thank Dr. Landry and colleagues [...]